Perdas produtivas em poedeiras comerciais em decorrência de estresse por calor - Oliveira, Jaime Augusto de (2017)
Despite the evolution of consumption and egg production in Brazil in recent years, investments in welfare and animal environment are few, making the activity vulnerable to climatic variations. This thesis aims review the heat impact in egg production, evaluate productive losses and laying mortality due heat stress, using data from meteorological stations. The results and the review that are part of this thesis are presented in scientific articles. The literature review discusses the issue of animal welfare and the impact of climatic variations on egg production and consumption. The second article evaluates the influence of environmental variables of the same day and days before the posture, on productivity. And the third article classifies the occurrence of high mortality of laying hens in weather conditions that could potentially trigger thermal stress. The database used consisted of data from an egg producing company, incorporated into the expected production data obtained from lineage manuals and data from meteorological stations near the farms. Data analysis was done using the data mining technique, using two classes for both productivity and mortality. The root node of the trees of productivity and mortality classification reinforces that the occurrence of Temperature Humidity Index (THI) values equal or above 23 ºC, triggers heat stress, influencing the productivity and mortality of commercial laying hens. The meteorological data from nearby stations and the producing data of commercial laying hens farms present patterns that allowed the development of understandable and relevant models to estimate falls in production and the occurrence of high mortality caused by climatic events of heat. Light and semi-heavy commercial laying hens had a reduction in productivity with THI values greater than 23º C. Layers housed on farms over 21 weeks showed increased mortality when it occurred for at least one hour with 23º C of THI.